Resistance to Glyphosate in Populations of Digitaria insularis - COSTA,N.V. (2018)
ABSTRACT: The intensive use of glyphosate can select resistant populations. This study aimed at evaluating the occurrence of glyphosate resistance in populations of D. insularis in agricultural areas. Three experiments were conducted in randomized block experimental design with four replications. The Resistance Degree (RD) was determined by a dose-response curve in the evaluated populations: Experiment 2012, São Camilo (R01 and R02) and Palotina (R03, R04 and S05-susceptible); Experiment 2013 Palotina (R06 and R12), Katueté/Paraguay (R07), Toledo (R08 and R10), Cascavel (R09), São Miguel do Iguaçu (R11), Dom Eliseu/Pará (S13-susceptible); Experiment 2015 Nova Aurora (R14), Iracema do Oeste (R15 and R16), Jesuitas (R17 and R18), Tupãssi (R19), Jotaesse (R20), Espigão Azul (R21) and Palmitopolis (S22- susceptible). In 2012, it was possible to confirm a moderate resistance (RD = 1.1 to 5.0) only in R03; and populations R01, R02 and R04 were highly resistant (RD>5.0). In 2013, populations R09, R10, R11 and R12 showed resistance, while R06, R07 and R08 were highly resistant. In 2015, the R14, R16, R18, R19 and R20 populations showed moderateresistance, and R15 and R18 were highly resistant. Only R21 was susceptible. It was found that 83% of producers use the no-tillage system, 100% use the succession soybean/corn with 90% transgenic varieties, 45% of producers cannot explain the procedure regulation/sprayer calibration. Around 62% use practices to prevent the selection of resistant biotypes. Resistance was confirmed in 89.5% of the populations. The adopted agronomic practices may explain these results.